PHYSICOCHEMICAL STUDY OF MULTICOLOR BORON CARBON OXYNITRIDE (BCNO) USING A UREA COMBUSTION METHOD - A. (NIM : 20216020), FAUZIAH
Luminescence material has attracted considerable attention due to its stable, nontoxic, tunable emissions, and low cost synthesis process. Boron Carbon Oxynitride (BCNO) is one of the luminescence materials that are widely accepted as applications in the medical field and electronic device including as white LED applications. Nowadays, BCNO could obtain emissions range from violet to near-red emission. Some mechanisms have been proposed regarding to BCNO luminescence process. But till now there is no clear mechanism related to BCNO luminescence. In this study, BCNO was obtained by a heating process using furnaces. In this study, multi-color BCNO has been successfully synthesized using materials consisting of boric acid, urea, and PEG 20k. Then we obtained a powder sample. The sample was separated conventionally based on the emissions color for further analysis. BCNO synthesized by a simple method to study the physicochemical properties of BCNO and its relation to the resulted emission. In this study, BCNO was obtained by a urea combustion method. This method is one of the simple techniques to produce powder sample of BCNO. Multi-color emissions of BCNO were obtained by a process at 775 ˚C for 30 min and at 750 ˚C for 45 min. Precursors are dissolved in DI water. Some techniques, including PL spectrometers, SEM, EDX, XRD, and FTIR were performed to characterize emissions wavelength, morphology, crystal structure, chemical bonding, and atomic composition of multicolor BCNO. Samples with a heating temperature at 775 ˚C for 30 minutes produced emissions such as 413 nm (BNCO-U), 436 nm (BCNO-B), and 485 nm (BCNO-H) for violet, blue and green emissions, respectively. Synthesis with different heating temperatures and carbon/boron ratios were also performed to study the physicochemical properties of multicolor emission of BCNO. Sample was synthesized with a heating temperature at 750 ˚C for 45 minutes produced emissions such as 432 nm (BNCO-B), 483 nm (BCNO-H), and 511 nm (BCNO-K) for blue, green, and yellow emissions, respectively. SEM analysis presents the surface morphology of each multi-color BCNO sample, showed similar morphology structure with an irregular shape and some hollow part. In addition, EDX results showed the distribution of B, C, N and O elements in the sample. These EDX results are correlated to the PL spectrum showed increased boron/nitrogen (B/N) ratio resulted emission wavelengths become smaller or shifted to blue wavelength. This result indicates that the B/N ratio contributes to the multi-color emissions of BCNO. The XRD confirmed the crystal structure of the sample which corresponding to the crystal phases B2O3 and h-BN. These results showed that there is no change in the crystal structure of multi-color BCNO sample, respectively. In addition, chemical bonds such as the B-C and C-N bonds were seen in FTIR spectrum of multi-color BCNO indicate that BCNO has formed. Based on the results, PL spectrometer and atomic composition effect to the physicochemical characteristics of multi-color BCNO.